Keefektifan Pembelajaran Daring terhadap Hasil Belajar Siswa - Melasari, Fennyta; Agustina, Ririn; Anggraini, Novia; Juneti, Juneti; Berli, Ahmad; Adisel, Adisel (JOEAI (Journal of Education and Instruction), 2021)
The author's purpose of conducting this study was to analyze student learning outcomes on daily tests in social studies learning during the pandemic era whether student scores increased or decreased while students were studying using the online method. The method in this study using the observation method. The observation method is collecting data or information that must be carried out by making observations directly to the place to be investigated. The results of the study, based on student learning outcomes from grades 1-10 on daily tests 1 and 2, the value of students increased in social studies subjects for class VII. This is because students are accustomed to the conditions of learning from home so that they have adapted to study and take advantage of all existing facilities to help their learning process. In conclusion, the use of online learning methods is quite effective in supporting the effectiveness of learning, this is evidenced by the learning outcomes in the daily tests of students which have increased on the 1st daily test to the 2nd daily test. The application of the online method can be well received by students, especially at SMP Negeri 4 Bengkulu City in class VII so that students can adapt even though they do not study face-to-face (offline). Keywords: Learning Outcomes, Social Studies Lessons, Online